Anion‐Directed Entangling Coordination Networks: Luminescence Sensing and Magnetic Properties. Issue 8 (16th June 2016) - Li, Cheng‐Peng; Chen, Qi; Mu, Yu‐Hai; Du, Miao
Abstract: Solvothermal reactions of a bifunctional ligand 4‐(2‐ethyl‐1 H ‐imidazol‐1‐yl)benzoic acid (2‐Heiba) with Cu(NO3 )2 and Cu(OAc)2 afforded two coordination polymers, [Cu3 (2‐eiba)4 (NO3 )2 ]⋅ 5 DMF (1 ; DMF= N, N ‐dimethylformamide) and [Cu(2‐eiba)2 ] (2 ), respectively, which show a twofold interpenetrated 3D network and 2D+2D→3D polycatenated architecture. Complex1 is a potential luminescent detector for nitrobenzene and Fe III ions, whereby strong antiferromagnetic interactions are also found between the Cu II centers. Abstract : In a bind : Two anion‐directed entangling coordination networks have been prepared, one of which shows potential for applications in chemical sensors for nitrobenzene and Fe 3+ ions„ whereby strong antiferromagnetic interactions are also found between the Cu II centers (see figure).